On awe and awareness - the literary text in the classroom On awe and awareness - the literary text in the classroom - Lynn Mario T. Menezes de Souza (Ilha do Desterro, 2008)
The results of a two-year research1 carried out in State secondary and primary schools in São Paulo showed that the discourse of the Foreign Language teacher in these schools was marked by a search for transparent univocity which appeared as a desire for a monolithic and univocal view of the foreign language, a univocal teaching methodology and a univocal and transparent teacher-student hierarchy in the teaching-learning process. This search, however, was seen to be constantly cut short by the complex heterogeneity of the classroom (see Menezes de Souza 1995, and Grigoletto and Menezes de Souza 1995), which itself appeared as variable levels of teacher and learner knowledge, obscure, ill-defined or unreal teaching-learning objectives and a chronic misfit between the needs/expectations of the learner
and those of the teacher and/or school institution. The results of a two-year research1 carried out in State secondary and primary schools in São Paulo showed that the discourse of the Foreign Language teacher in these schools was marked by a search for transparent univocity which appeared as a desire for a monolithic and univocal view of the foreign language, a univocal teaching methodology and a univocal and transparent teacher-student hierarchy in the teaching-learning process. This search, however, was seen to be constantly cut short by the complex heterogeneity of the classroom (see Menezes de Souza 1995, and Grigoletto and Menezes de Souza 1995), which itself appeared as variable levels of teacher and learner knowledge, obscure, ill-defined or unreal teaching-learning objectives and a chronic misfit between the needs/expectations of the learner
and those of the teacher and/or school institution.